الاجتهاد المهني وعلاقته بالاقتراب المهني لدى الاطباء - عمرون, خالد (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2021)
هدفت الدراسة الى التعرف على علاقة الاجهاد المهني بالاغتراب المهني لدى الاطباء العاملين بالمؤسسة العمومية الاستشفائية بالمسيلة ومحاوله الخروج بتوصيات تساعد على الاستقرار المهني للأطباء وضمان استمرارهم داخل مكان عملهم. وتضمنت العينة 24 طبيب تم اختيارهم مع مراعاة عامل الخبرة والجنس، وكانت أدوات البحث المستخدمة هي استمارتين من اعداد الباحث، واحدة تقيس الاجهاد المهني لدى الطبيب احتوت على 18 عبارة، والثانية تقيس الاغتراب المهني لدى الطبيب تحتوي على 20 عبارة، و احتوت على أربع أبعاد هي: اللاهدف، العجز، غربة الذات، والتشاؤم، أما المنهج فكان الوصفي تحليلي ارتباطي. اعتمد الباحث على معامل الارتباط سبيرمان في تحليل نتائج المتوصل اليها. - من النتائج المتوصل اليها من خلال التحاليل الاحصائية كانت كالتالي: - توجد علاقه ارتباطية ضعيفة بين الاجهاد المهني والاغتراب المهني لدى الاطباء - توجد علاقه ارتباطية إيجابية قوية بين الاجهاد المهني ولا هدف - توجد علاقة ارتباطية إيجابية متوسطة بين عامل ايجاد المهني وعامل العجز لدى الاطباء - توجد علاقه ارتباطية إيجابية ضعيفة بين الاطباء وغربة الذات - العلاقة ارتباطية بين الاجهاد والمهني والتشاؤم لدى الاطباء هي علاقة ضعيفة تلامس الانعدام This study aimed to identify the relationship of occupational stress with occupational alienation among doctors working in the public hospital institution in M'sila and trying to come up with recommendations that help the professional stability of doctors and ensure their continuity within their workplace. The sample included 24 doctors who were selected taking into account the factor of experience and gender, and the research tools used were two forms prepared by the researcher, one measuring the occupational stress of the doctor and containing 18 phrases, and the second measuring the occupational alienation of the doctor containing 20 phrases, and it contained four dimensions: : aimlessness, helplessness, self-estrangement, and pessimism. As for the method, it was descriptive, analytical, and relational. The researcher relied on the Spearman correlation coefficient in analyzing the results. The results obtained through statistical analyzes were as follows: There is a weak correlation between occupational stress and occupational alienation among doctors There is a strong positive correlation between occupational stress and no goal - There is a medium positive correlation between the occupational finding factor and the disability factor among doctors There is a weak positive correlation between doctors and self-alienation The correlation between occupational stress and pessimism among doctors is a weak relationship that touches the absence Keywords: occupational stress, occupational alienation En savoir plus sur ce texte sourceVous devez indiquer le texte source pour obtenir des informations supplémentaires Envoyer des commentaires Panneaux latéraux
Keywords: Occupational stress, occupational alienation الإجهاد المهني، الاغتراب المهني